Molecular imaging of neuroinflammation in patients after mild traumatic brain injury: a longitudinal 123I‐CLINDE single photon emission computed tomography study. (21st May 2019) - Ebert, S. E.; Jensen, P.; Ozenne, B.; Armand, S.; Svarer, C.; Stenbaek, D. S.; Moeller, K.; Dyssegaard, A.; Thomsen, G.; Steinmetz, J.; Forchhammer, B. H.; Knudsen, G. M.; et al.
Abstract : Background and purpose: Neuroinflammation has been proposed as part of the pathogenesis of post‐concussion symptoms (PCS), but the inflammatory response of the human brain to mild traumatic brain injury (mTBI) remains unknown. We hypothesized that a neuroinflammatory response is present in mTBI at 1–2 weeks post‐injury and persists in patients with PCS. Methods: We scanned 14 patients with mTBI without signs of structural damage at 1–2 weeks and 3–4 months post‐injury and 22 healthy controls once using the single photon emission computed tomography tracer 123 I‐CLINDE, which visualizes translocator protein (TSPO), a protein upregulated in active immune cells. PCS was defined as three or more persisting symptoms from the Rivermead Post Concussion Symptoms Questionnaire at 3 months post‐injury. Results: Across brain regions, patients had significantly higher 123 I‐CLINDE binding to TSPO than healthy controls, both at 1–2 weeks after the injury in all patients ( P = 0.011) and at 3–4 months in the seven patients with PCS ( P = 0.006) and in the six patients with good recovery ( P = 0.018). When the nine brain regions were tested separately and results were corrected for multiple comparisons, no individual region differed significantly, but all estimated parameters indicated increased 123 I‐CLINDE binding to TSPO, ranging from 2% to 19% in all patients at 1–2 weeks, 13% to 27% in patients with PCS at 3–4 months and −9% to 17% in patients with good recovery at 3–4 months. Conclusions: Neuroinflammation was present in mTBI at 1–2 weeks post‐injury and persisted at 3–4 months post‐injury with a tendency to be most pronounced in patients with PCS.